Studies on Arabic Dialectology and Sociolinguistics : Proceedings of the 12th International Conference of AIDA held in Marseille from May 30th to June 2nd 2017 - Marie-Aimée Germanos (Institut de recherches et d'études sur les mondes arabes et musulmans, 2019)
This volume contains over fifty articles related to various fields of modern Arabic dialectology. All the articles are revised and enhanced versions of papers read on the 12th Conference of the Association Internationale de Dialectologie Arabe (AIDA) held in Marseille in June 2017. Since its first conference in Paris in 1993, AIDA members gather every two years in different country. The collection of the AIDA proceedings offer an updated insight of the development of the field. During the past few decadesthe the study of Arabic dialects has become an important branch of research covering a wide range of subjects from phonological analyses, morphosyntax, semantics to pragmatics, sociolinguistics, folk linguistics, studies on literacy and writings, cultural and artistic practices, etc. As many articles of this volume illustrate, the study of Arabic dialects explores different aspects of the languages and cultures of the contemporary Arab world. A remarkable feature is the growing and constant participation of young scholars from all around the globe.